Challenges and Opportunities for Treating Intrahepatic Cholangiocarcinoma - Serifis N; Tsilimigras DI; Cloonan DJ; Pawlik TM (Hepatic Medicine: Evidence and Research, 2021)
Nikolaos Serifis,1 Diamantis I Tsilimigras,2 Daniel J Cloonan,3 Timothy M Pawlik2 1Center for Transplantation Sciences, Massachusetts General Hospital, Boston, MA, USA; 2Department of Surgery, The Ohio State University Wexner Medical Center, Columbus, OH, USA; 3Department of Surgery, Beth Israel Deaconess Medical Center, Boston, MA, USACorrespondence: Diamantis I TsilimigrasDepartment of Surgery, The Ohio State University, Wexner Medical Center, 410 W 10th Avenue, Columbus, OH, 43210, USATel +1 215 987 9177Email diamantis.tsilimigras@osumc.eduAbstract: Intrahepatic cholangiocarcinoma (ICC) is one of the rarest and most aggressive types of cancer. The symptoms of ICC patients can be vague, leading to late diagnosis and dismal prognosis. In this review, we investigated the treatment options for ICC, as well as ways to overcome challenges in identifying and treating this disease. Imaging remains the gold standard to diagnose ICC. Patients are staged based on the tumor, nodes and metastases (TNM) staging system. Patients eligible for surgical resection should undergo surgery with curative intent with the goal of microscopically disease-free margins (R0 resection) along with lymphadenectomy. Minimal invasive surgery (MIS) and liver transplantation have recently been offered as possible ways to improve disease outcomes. ICC recurrence is relatively common and, thus, most patients will need to be treated with systemic therapy. Several clinical trials have recently investigated the use of neoadjuvant (NT) and adjuvant therapies for ICC. NT may offer an opportunity to downsize larger tumors and provide patients, initially ineligible for surgery, with an opportunity for resection. NT may also treat occult micro-metastatic disease, as well as define tumor biology prior to surgical resection, thereby decreasing the risk for early postoperative recurrence. Adjuvant systemic therapy may improve outcomes of patients with ICC following surgery. Ongoing clinical trials are investigating new targeted therapies that hold the hope of improving long-term outcomes of patients with ICC.Keywords: liver, intrahepatic cholangiocarcinoma, resection, outcomes